Da li je hipertekstualni koautor dihotoman? - Hromadžić, Hajrudin (Monitor ISH, 2004)
Is the hypertextual coauthor dichotomous? The paper focuses on the concept of the hypertextual coauthor or "writereader", which has emerged as a type of new media identity in the theory of the hypertext. This identity is created with the aid of contemporary digital computer technology, which permits a dynamic interaction between the author/writer and the reader/consumer of the text. I discuss the related concept of interactivity and the concept of interpassivity; explore the position and function of the computer screen as the "natural" environment of the hypertext; and apply Lacan's concept of gaze to the differences between the TV and computer screens. Finally, I define the concepts of virtual reality and the virtual subject.
Keywords: hypertext; hipertekst; interaktivnost; hipertekstualni koavtor; interpasivnost; virtualni subjekt